2016
DOI: 10.3389/fpsyg.2016.01686
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Structure, Path Characteristics, and Perceptual Grouping in Immediate Serial Spatial Recall

Abstract: Immediate serial spatial recall measures the ability to retain sequences of locations in short-term memory and is considered the spatial equivalent of digit span. It is tested by requiring participants to reproduce sequences of movements performed by an experimenter or displayed on a monitor. Different organizational factors dramatically affect serial spatial recall but they are often confounded or underspecified. Untangling them is crucial for the characterization of working-memory models and for establishing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 55 publications
(177 reference statements)
1
12
0
Order By: Relevance
“…Lastly, consistent with previous evidence (De Lillo, Kirby, & Poole, 2016;Kemps, 2001;Pieroni et al, 2011;Rossi-Arnaud et al, 2006;Rossi-Arnaudet et al, 2012), we found that order memory was significantly better for symmetrical arrays (both vertical and horizontal) than for random arrays, confirming that our participants took advantage of the structural properties of symmetrical patterns to enhance immediate spatial recall. Most importantly, we showed that pointing movements impaired memory for all types of arrays to the same extent, as indicated by the absence of significant interactions between stimulus type and encoding condition.…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, consistent with previous evidence (De Lillo, Kirby, & Poole, 2016;Kemps, 2001;Pieroni et al, 2011;Rossi-Arnaud et al, 2006;Rossi-Arnaudet et al, 2012), we found that order memory was significantly better for symmetrical arrays (both vertical and horizontal) than for random arrays, confirming that our participants took advantage of the structural properties of symmetrical patterns to enhance immediate spatial recall. Most importantly, we showed that pointing movements impaired memory for all types of arrays to the same extent, as indicated by the absence of significant interactions between stimulus type and encoding condition.…”
Section: Discussionsupporting
confidence: 92%
“…In this way, a temporal structure of the place is created through eye movements (Rucci et al, 2018;Heuer and Rolfs, 2019), where a swap of object locations results in a swap along the temporal dimension. Usually such temporal encoding of space is evident when stimuli dynamically appear and disappear or are highlighted, in a sequence (De Lillo et al, 2016) and has its own independent contribution to memory from concurrently formed spatial representations (Heuer and Rolfs, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they suggest that, for humans, the distance travelled is not the main factor that allows the reduction of memory load in this type of tasks. Rather, using a path that is compatible with the hierarchical coding of a patchy environment is more effective than using a shorter one (De Lillo et al, 2014;De Lillo et al, 2016). Detailed analyses of response times when patch size and number of parches is manipulated confirm the hierarchical nature of representations of these arrays in serial recall (De Lillo & Lesk, 2011).…”
Section: Travelling Distance and Memory Load In Serial Recallmentioning
confidence: 97%
“…The results of experiments where different sequence characteristics were manipulated, such as their path length and their conformity to a linear organisation (e.g. sequences with or without consecutive steps within the same row or column), show that linear organisation explains a larger portion of variance in recall than path length in humans (De Lillo et al, 2016).…”
Section: Travelling Distance and Memory Load In Serial Recallmentioning
confidence: 99%